2004
DOI: 10.1021/jf034989v
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Functional Expression, and Characterization of Cystatin in Sesame Seed

Abstract: A cDNA fragment encoding cystatin, a cysteine protease inhibitor, was obtained from maturing sesame seeds. The clone was constructed in a nonfusion or fusion vector and then overexpressed in Escherichia coli. The recombinant cystatins were found in the soluble fraction of cell extract and were demonstrated to be functionally active in a reverse zymographic assay. The corresponding endogenous 22 kDa cystatin of low abundance in mature seeds was purified to homogeneity via a papain-coupling affinity column and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 40 publications
3
39
0
1
Order By: Relevance
“…The mTaMDC1 constant was lower than the Ki value reported for WC5 (10 À6 M; Corre-Menguy et al 2002), but higher than those of rice OC I (3.0·10 À8 M; Kondo et al 1990) and maize CC I (2.3·10 À8 M; Abe et al 1994). Comparison of papain inhibition activity of 23 kDa cystatins showed that the Ki of mTaMDC1 was in the same order as soybean cystatin (1.9·10 À7 M; Misaka et al 1996), but higher than cystatins from sesame (2.7·10 À8 M; Shyu et al 2004) and strawberry (1.9·10 À9 M; Martinez et al 2005a).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The mTaMDC1 constant was lower than the Ki value reported for WC5 (10 À6 M; Corre-Menguy et al 2002), but higher than those of rice OC I (3.0·10 À8 M; Kondo et al 1990) and maize CC I (2.3·10 À8 M; Abe et al 1994). Comparison of papain inhibition activity of 23 kDa cystatins showed that the Ki of mTaMDC1 was in the same order as soybean cystatin (1.9·10 À7 M; Misaka et al 1996), but higher than cystatins from sesame (2.7·10 À8 M; Shyu et al 2004) and strawberry (1.9·10 À9 M; Martinez et al 2005a).…”
Section: Discussionmentioning
confidence: 98%
“…2). Comparison of TaMDC1 with some of a non cereal 23 kDa cystatins characterized so far showed 65, 64, 62, 62, 61, 59% identity with cystatin from cabbage (Lim et al 1996), sesame (Shyu et al 2004), apple (Ryan et al 2003), soybean (Misaka et al 1996), taro (Yang and Yeh 2005), and strawberry (Martinez et al 2005a), respectively (Fig. 2).…”
Section: Cdna Isolation and Sequence Analysesmentioning
confidence: 91%
See 1 more Smart Citation
“…Several members of this family have been characterized in various plant species, and homology with animal cystatins has been described (Margis et al 1998). Most of phytocystatins are small proteins, ranging in size from 12 to 16 kDa, with a distinct group having a higher molecular weight (*23 kDa) due to a C-terminal extension (Shyu et al 2004;Margis-Pinheiro et al 2008). Several multicystatins with up to eight cystatin domains have been reported, particularly in tomato (Wu and Haard 2004).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The use of seeds as host organ for recombinant protein production can be advantageous as they are natural storage organs with high expression levels, but this can be a challenge for downstream processing when the protein of interest has to be purified from the seed extract. 8 Soybean seeds contain more protein than any other commercial crop (up to 48%) consisting of a mixture of proteins (α-, β-, and γ -conglycinin, glycinin and other globulins) ranging in molecular weight from 140 to 300 kDa with different physicochemical properties allowing fractionation and differentiation.…”
Section: Introductionmentioning
confidence: 99%